Pengaruh Keselamatan Dan Kesehatan Kerja (K3) Dan Motivasi Kerja Terhadap Kinerja Karyawan PT Panca Darma Sejati - Sari, Purnama; Karlina , Eulin (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Good human resources and have a strategic approach context, and good workforce in the learning process. The purpose of this study was to determine the influence of occupational safety and health (K3) and work motivation on employee performance at PT. Panca Darma Sejati Bekasi Regency. The method used in this study is a quantitative method and uses a total saturated sample of 72 respondents and data collection using observation, interview and questionnaire techniques. The results of the study using the T test showed that the results of occupational safety and health (K3) were 6.130 and significant 0.000. So, 6.130> 1.995 and significant 0.000 <0.05, then the variable occupational safety and health (K3) has an effect and is significant on employee performance, while work motivation with results of 8.426 and significant 0.000. So, 8.426>1.995 and significant 0.000<0.05, then that the work motivation variable has an effect and is significant to employee performance. The results for the F test on the variables of occupational safety and health (k3) and work motivation are 44.741 so, 44.741>3.130 and significant v0.000<0.05, then simultaneously have an effect and are significant. The results of the determination test are explained by occupational safety and health (k3) and work motivation by 56.5% while the remaining 43.5% influenced by variables outside this study.